MODEL INTEGRASI ILMU DAN PENGEMBANGANNYA DI FAKULTAS SYARI’AH DAN HUKUM UIN AR-RANIRY BANDA ACEH DAN UIN SUMATERA UTARA - Tarmizi M Jakfar; Fuad Ramly; Maimun Fuadi; Jabbar Sabil (Islam Futura, 2019)
Integration of science is a central issue in the arena of the State Islamic University (UIN) in Indonesia, including UIN Ar-Raniry and UIN North Sumatra. One of the main problems that is increasingly discourse is the model of the integration of knowledge that is put in place and the development efforts implemented. Although UIN Ar-Raniry has an integration model of "Frikatifisasi Ilmu" and UIN North Sumatra with the "Integrative Transdisciplinary" model, the Syari'ah Faculty academics and the second Law of the UIN generally do not understand it definitively, so that the integration model does not play an effective role in the process integration of sciences. Therefore, constructive evaluation, comprehensive socialization, and a more intensive development strategy involve all related components. The expected goal of this study is to present a description of the integration model of science that is valid and understood in the second FSH of the UIN, along with its implementation and development in the present. As a qualitative study, this study uses descriptive, interpretative, and comparative analysis methods / techniques. The data analyzed mainly comes from the results of interviews with lecturers and FGDs with students of the School of Comparative Study Program and the FSH State Law Study Program, in addition to other related data.